MALDI-TOF mass spectrometry in the 21st century. (27th October 2022) - Dueñas, Maria Emilia; Trost, Matthias
Abstract : This year marks the 20th anniversary of Koichi Tanaka securing the Nobel Prize in chemistry, shared with John Fenn and Kurt Wüthrich, for demonstrating the applicability of laser technology to analyze biological macromolecules. The principle of laser desorption is fundamental for many of today's analytical methods such as matrix-assisted laser desorption/ionization (MALDI). In this article, we provide an overview of MALDI and highlight the power, versatility and range of applications within the biochemistry community.